Inovasi Tren Kuliner Tahu Crispy Balado Dalam Membangun Peluang Bisnis Cemilan - Arsita, Ulfa; Mika, Tiara; Lestari, Mitha; Annisa; Hismawati; Marwa; Sapar (Pencerah, 2023)
The Innovation of Crispy Tofu Balado Culinary Trend as a Snack Business Opportunity. The purpose of the Student Entrepreneurship Creativity Program (PKM-K) is to motivate students to become entrepreneurs by developing the Crispy Tofu Balado Culinary Trend as a Snack Business Opportunity. Crispy Tofu Balado is very beneficial for health, as it contains a lot of protein and nutrients for the body, minimizes the risk of various diseases, and creates new business opportunities. The implementation method of this program includes input, process (production), output, and evaluation. The result of this program includes conducting market surveys to determine the market conditions, feasibility studies of the business to be run, selection of ingredients and provision of a place, and facilities to support the production process. The production process involves preparing the ingredients and making Crispy Tofu Balado until it is ready to be marketed. The output is the finished Crispy Tofu Balado product that is ready to be used and marketed to consumers. Finally, the evaluation stage is conducted after the production of the product to review any shortcomings that make consumers uncomfortable using our product. In conclusion, the PKM-K program on the Innovation of Crispy Tofu Balado Culinary Trend as a Snack Business Opportunity can provide students with skills to remain innovative and creative in developing the Crispy Tofu Balado Culinary Trend, give students the opportunity to practice entrepreneurship with a comprehensive understanding of the concept of entrepreneurship, and build student motivation to continue in business